Effect of fire on viability and germination behaviour of Cistus ladanifer and Cistus salvifolius seeds - Aguayo-Villalba, Antonio Ángel; Álvarez-Gómez, Concepción María; Barroso-Rodríguez, Laura María; Camacho-López, Samuel; Cocero-Ramírez, Agustín; Sánchez-Romero, Carolina (Springer, 2021)
Fire is a natural phenomenon that is very frequent in ecosystems of the Mediterranean basin. Cistus ladanifer and C. salvifolius (Cistaceae family) are evergreen shrubs and components of plant communities found in this region. The objective of this study was to evaluate the effect of fire on the germination of C. ladanifer and C. salvifolius seeds. For this purpose, seeds of both species were subjected to different heat-shock treatments simulating natural fire conditions (50–175°C for 1 and 5 min). To elucidate the ecological significance of the effects of fire, viability and different traits informative about the dynamics of the germination process, such as final germination percentage (FGP), first day of germination (FDG), last day of germination (LDG), time spread of germination (TSG) and coefficient of velocity of germination (CVG), were determined. Seeds of both species exhibited fire-related behaviour, as they showed seed heat resistance and heat-stimulated germination. Germination in control, untreated seeds was very low, with 10 and 0% FGP for C. ladanifer and C. salvifolius, respectively. Thermal treatments significantly increased germination in both cases, with optimal results achieved at 100–125°C for 1 min and 75–100°C for 5 min. Under these conditions, greater germination percentages were obtained in C. salvifolius (92–95%) than in C. ladanifer (64–68%). Temperature proved to have a greater influence on seed viability and germination than the accumulated heat dose. The pattern of seed germination varied depending on the species and the heat shock treatments. In general, C. ladanifer exhibited earlier and faster germination. These characteristics, along with the high number of seeds produced per plant, make C. ladanifer a more competitive species for colonizing empty spaces after fire.
Keywords: Semillas - Dormancia; Plantas - Efectos del fuego; Dormancy; Fire; Germination; Germination kinetics; Heat index; Cistus